2015
DOI: 10.1117/1.jbo.20.12.121311
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional fuse deposition modeling of tissue-simulating phantom for biomedical optical imaging

Abstract: Abstract. Biomedical optical devices are widely used for clinical detection of various tissue anomalies. However, optical measurements have limited accuracy and traceability, partially owing to the lack of effective calibration methods that simulate the actual tissue conditions. To facilitate standardized calibration and performance evaluation of medical optical devices, we develop a three-dimensional fuse deposition modeling (FDM) technique for freeform fabrication of tissue-simulating phantoms. The FDM syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…Direct printing of gel wax could be useful to create structures with greater 3D complexity. One recent step in this direction was provided by Dong et al ( 2015 ), who developed a fuse deposition modelling system to fabricate 3D heterogeneous phantoms for optical imaging. Gel wax was mixed with additives and directly printed using a custom print head with multiple channels and an embedded mixing device.…”
Section: Discussionmentioning
confidence: 99%
“…Direct printing of gel wax could be useful to create structures with greater 3D complexity. One recent step in this direction was provided by Dong et al ( 2015 ), who developed a fuse deposition modelling system to fabricate 3D heterogeneous phantoms for optical imaging. Gel wax was mixed with additives and directly printed using a custom print head with multiple channels and an embedded mixing device.…”
Section: Discussionmentioning
confidence: 99%
“…To minimise bubble formation, mixing and pouring of gel wax compositions within low pressure chambers could be advantageous. For more anatomical realism, wall-less, fluid-filled vessels could be used [ 32 , 43 ], osseous structures could be incorporated with 3D printed polymers [ 44 ], and gel wax could even be directly 3D printed [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The IAD algorithm iteratively searches for a solution to the radiative transfer equation (RTE) under the assumption of layered samples with homogeneous optical properties and uniform light illumination. The scattering anisotropy factor ( g ) was assumed to be g = 0.6 and the refractive index for gel wax was set to 1.469 [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several years ago, we pioneered the use of this approach for fabrication of turbid, tissue-simulating biophotonic phantoms [14] and provided preliminary images of linear channel phantoms with hyperspectral imaging and optical coherence tomography. Subsequently, additional studies have reported the development of 3D-printed phantoms for optical coherence tomography [15], diffuse optical tomography [16,17], and hyperspectral reflectance imaging [18]. Other studies have used 3D-printing to generate molds for phantom fabrication, including photoacoustic imaging applications [19,20].…”
Section: Introductionmentioning
confidence: 99%